Answer:
Therefore the Final Solution is
x = 1 and y = 1
Step-by-step explanation:
Given:
...............Equation ( 1 )
................Equation ( 2 )
To Find:
x = ?
y = ?
Solution:
Equating Equation ( 1 ) in Equation ( 2 ) we get
Now Substituting y = 1 in Equation ( 1 ) we get
Therefore the Final Solution is
x = 1 and y = 1
Answer:
n (A' U B ) = 75
Step-by-step explanation:
Here, given : n(U)=120, n(A)=45, and n(B)=50
As we know:
n (A ' U B) = n(A) − n (A∩B) ... (1)
Here, n(A) = 45
So, n( A') = n(U) - n(A) = 120 - 45 = 75
⇒ n(A') = 75
Now, as given A and B are disjoint sets.
⇒ n (A ∩ B) = Ф
So, (A' U B ) = A'
So, n (A' U B ) =n( A') = 75
⇒ n (A' U B ) = 75